Digital Marketing of UMKM Tugu Hydroponics through Social Media in Tugu Village, Sliyeg Sub-District, Indramayu District 2023 - Muryono, Muryono; Andryani, Kristina; Yusfiarista, Erlika (Asian Journal of Management Analytics, 2025)
Digital marketing through Facebook social media has become an important strategy for Micro, Small and Medium Enterprises (MSMEs) in expanding their reach and building relationships with customers. In this context, this study explores how Tugu Hidroponik MSMEs use the Facebook platform as a key tool for their digital marketing. Through a qualitative approach, data was collected through interviews with business owners and analysis of their social media content. The results show that Tugu Hidroponik MSMEs have successfully utilized Facebook's interactive features to increase interaction with customers, present relevant content, and expand their market share. The findings provide insights into how MSMEs can optimize their digital marketing through social media, with a particular emphasis on the Facebook platform, to increase their brand visibility and business growth.